Multidisciplinary approach to chest wall reconstruction in primary breast angiosarcoma resection. Issue 5 (6th May 2020) - O'Donnell, John Phineas; Sugrue, Ryan; McLaughlin, Ray; McInerney, Niall M
Abstract : Angiosarcomas account for less than 1% of primary breast cancers. Typically, they occur in young women with a low-risk personal or family history. Diagnosis, resection and reconstruction require a multidisciplinary team of breast surgeons, oncologists and plastic reconstructive surgeons. Cross-disciplinary awareness among these specialities enables dimensional patient treatment. We report a case of primary angiosarcoma of the breast in a 33-year-old woman, with no previous radiotherapy exposure, treated with a radical mastectomy and chest wall reconstruction with a deep inferior epigastric perforator (DIEP) Flap. There is a general consensus in current literature regarding the difficulty for curative treatment in angiosarcomas. There is a requirement for surgical intervention to be aggressive to ensure oncological clearance. Subsequently, the extensive reconstructive task proves a major procedure for any plastic surgeon. DIEP autologous flap chest wall reconstruction accompanying radical mastectomy can be used in efforts to eradicate risks of deep margin incomplete excision in breast angiosarcomas. This case report and review of the current literature aim to provide guidance for colleagues managing angiosarcomas and also highlight the versatility of the DIEP flap.